2007
DOI: 10.1016/j.jsv.2006.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Vibration absorbers for chatter suppression: A new analytical tuning methodology

Abstract: Vibration absorbers have been widely used to suppress undesirable vibrations in machining operations, with a particular emphasis on avoiding chatter. However, it is well known that for vibration absorbers to function effectively their stiffness and damping must be accurately tuned based upon the natural frequency of the vibrating structure. For general vibration problems, suitable tuning strategies were developed by Den Hartog and Brock over 50 years ago. However, the special nature of the chatter stability pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(111 citation statements)
references
References 21 publications
3
97
0
2
Order By: Relevance
“…Figure 1 shows the stability chart in the dimensionless space Ω d , p (Ω d is the dimensionless spindle speed) for a system without and with LTVA and clearly illustrates the advantage given by the absorber in terms of stability. Equations for obtaining an almost optimal linear tuning of the absorber are given in [5] .…”
Section: Mechanical Model and Stability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the stability chart in the dimensionless space Ω d , p (Ω d is the dimensionless spindle speed) for a system without and with LTVA and clearly illustrates the advantage given by the absorber in terms of stability. Equations for obtaining an almost optimal linear tuning of the absorber are given in [5] .…”
Section: Mechanical Model and Stability Analysismentioning
confidence: 99%
“…These include conventional mechanical linear vibration absorbers [5] , vibro-impact absorbers [6] , friction damping absorbers [7] , self-tunable absorbers [8] , piezoelectric absorbers based on shunt circuits [9] and nonlinear energy sinks [10] . Numerical and experimental studies exhibited their promising performance in terms of stabilization of machining operations, allowing larger depth of cut in stable conditions, which enables to increase production speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, continuous improvement has been achieved in the chatter control of boring, including sophisticated methods, such as the use of electro-rheological [28] and magneto-rheological fluids [29] and active dynamic absorbers [30][31][32][33]. However, the use of passive dynamic absorbers [34][35][36][37][38][39] is a simple solution and it is still a promising field of research for chatter suppression, not only in boring operations.…”
Section: Introductionmentioning
confidence: 99%
“…Lee [37] demonstrated that the dynamic response of the cutting tool was improved due to the presence of a passive absorber when the natural frequency of the dynamic vibration absorber was close to the natural frequency of the cutting tool and the absorber had a large damping ratio. Sims [38] proposed an analytical method relevant for a wide range of machining-chatter problems. In turning and boring operations, passive vibration absorbers can be tuned using the analytical technique developed in [38].…”
Section: Introductionmentioning
confidence: 99%